Autonomous transformation : creating a more human future in the era of artificial intelligence - Evergreen, Brian, ....- (New Jersey : John Wiley & Sons, Inc., 2023)
From technologist and strategist Brian Evergreen, a bold new agenda for the role of organizational leaders in creating a more human future with technology Social good initiatives are incompatible with the current network of systems that make up and support the private and public sectors. Millions of dollars have been invested in bringing leaders together from organizations around the world to design solutions for global challenges such as the climate crisis, child labor, racism, war, and many more. Despite executive buy-in, alignment of core capabilities and resources, passionate leadership, and well-designed strategies, these initiatives inevitably fail (with a few, notable exceptions). The dawn of the Internet ignited a global redesign and rebuild of the interlocking systems that make up and support the private and public sectors today. The era of Digital Transformation extended this further through the adoption of cloud technologies and distributed computing. With a recent wave of technological advancements, organizations have arrived at another global redesign and rebuilding of the network of systems that make up society: Autonomous Transformation, revealing an opportunity for leaders to create Profitable Good through systemic design in combination with emerging autonomous technologies and surprising and remarkable partnerships. Autonomous Transformation provides a blueprint for leaders and managers who have aspired or attempted to harness artificial intelligence and its adjacent technologies for the betterment of their organization and the world, weaving strategy, business, economics, systemic design, and philosophy into four actionable steps with accompanying frameworks: Clear the Digital Fog See the Systems Choose a Problem Future Design Inevitability.
Keywords: Artificial intelligence; Business enterprises